The expression of GapA and CrmA correlates with the Mycoplasma gallisepticum in vitro infection process in chicken TOCs - Nancy Rüger; Michael P. Szostak; Silke Rautenschlein (Veterinary Research, 2022)
Abstract Mycoplasma (M.) gallisepticum is the most pathogenic mycoplasma species in poultry. Infections cause mild to severe clinical symptoms associated with respiratory epithelial lesion development. Adherence, biofilm formation, and cell invasion of M. gallisepticum contribute to successful infection, immune evasion, and survival within the host. The important M. gallisepticum membrane-bound proteins, GapA and CrmA, are key factors for host cell interaction and the bacterial life-cycle, including its gliding motility, although their precise role in the individual infection step is not yet fully understood. In this study, we investigated the correlation between the host–pathogen interaction and the GapA/CrmA expression in an environment that represents the natural host’s multicellular compartment. We used an in vitro tracheal organ culture (TOC) model, allowing the investigation of the M. gallisepticum variants, Rlow, RCL1, RCL2, and Rhigh, under standardised conditions. In this regard, we examined the bacterial adherence, motility and colonisation pattern, host lesion development and alterations of mucociliary clearance. Compared to low virulent RCL2 and Rhigh, the high virulent Rlow and RCL1 were more efficient in adhering to TOCs and epithelium colonisation, including faster movement from the cilia tips to the apical membrane and subsequent cell invasion. RCL2 and Rhigh showed a more localised invasion pattern, accompanied by significantly fewer lesions than Rlow and RCL1. Unrelated to virulence, comparable mucus production was observed in all M. gallisepticum infected TOCs. Overall, the present study demonstrates the role of GapA/CrmA in virulence factors from adherence to colonisation, as well as the onset and severity of lesion development in the tracheal epithelium.